The effect of cassava leaves extract on pharmacokinetics profile of rutin plasma - Nugrahaningsih, WH; Fatimatuz Zahroh; Lisdiana; Ari Yuniastuti; Rudyatmi, Ely (Penerbit Universiti Kebangsaan Malaysia, 2019)
The leaves of cassava are used as traditional medicine, to treat ringworm, tumor, abscess, conjunctivitis, sores, headaches, rheumatism and fever diseases in several countries. Phytochemical investigations showed that flavonoids and Rutin constituents of the cassava leaves, berths the need for data as regards safety, effectiveness, toxicity and pharmacokinetics for its usage as herbal medicine. The purpose of this research was to observe pharmacokinetic parameters of Rutin in rat plasma, after oral administration of cassava leaves extract. Pharmacokinetics indicators for absorption was (Cmax, tmax, and AUC0-24h), while elimination was (Ke and t1/2). 14 healthy male Wistar rats were divided into 7 groups (each group with 2 rats), after which a single dose (600 mg) of cassava leaves extract was given orally. Thereafter, blood samples of the wistar rats were collected and separated at different time intervals (0; 0.5; 1; 2; 4; 6; 12; and 24 h). Using HPLC-UV-VIS method, the resulting plasma was analyzed for Rutin concentration. The analysis showed Rutin concentration at 0 mg/mL (0 h), 0.151 mg/mL (0.5 h), 0.176 mg/mL (1 h), 0.18 mg/mL (2 h), 0.184 mg/mL (4 h), 0.163 mg/mL (6 h), 0.15 mg/mL (12 h) and 0.1225 mg/mL (24 h). The main pharmacokinetic parameters were; Cmax 0.184 mg/mL recorded 4 h (tmax) after oral administration; AUC0-24 was 3.583 mg h/mL and t1/2 was 94.54 h. The study concluded that Rutin of cassava leaves extract, reached maximum concentration within 4 h after oral administration and was inside in the plasma for more than 24 h. Hence, it is recommended to consume cassava leaves extract as herbal medicine, only once a day.